2020
DOI: 10.1007/s12105-020-01131-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuroepithelial Structures of the Oral Soft Tissues Including the Juxtaoral Organ of Chievitz: A Literature Review and Audit of Diagnosed Cases

Abstract: The juxtaoral organ of Chievitz (JOOC) is a part of microanatomy composed of bland epithelial islands closely associated with small nerves and usually described within the soft tissue on the lingual aspect of the posterior mandible. Similar structures are documented in the posterior tongue. There is a risk of misinterpretation as carcinoma showing perineural invasion. An audit was undertaken of diagnosed cases of the JOOC and similar neuroepithelial structures identified within the oral soft tissues of surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In an extensive literature review, Kennedy [ 2 ] reported that the most commonly described anatomical location of the juxtaoral organ is lingual to the mandible, but in keeping with published cases, it can also be found buccal to the mandible and in the posterior tongue.…”
Section: Juxtaoral Organ Anatomymentioning
confidence: 74%
See 4 more Smart Citations
“…In an extensive literature review, Kennedy [ 2 ] reported that the most commonly described anatomical location of the juxtaoral organ is lingual to the mandible, but in keeping with published cases, it can also be found buccal to the mandible and in the posterior tongue.…”
Section: Juxtaoral Organ Anatomymentioning
confidence: 74%
“…The procedure of differential diagnosis, ensuring there is no misinterpretation and thus correctly identifying this organ, lies in the understanding of its anatomical, morphological and cytological features; clinical features are rarely helpful [ 4 , 5 , 14 , 22 ]. Kennedy [ 2 ], when identifying the standard for the correct juxtaoral organ diagnostic procedure, emphasized the fact that morphological and anatomical criteria, in contrast to clinical features, may help to differentiate between the juxtaoral organ and infiltrating carcinoma, as summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations